Lipid-lowering activity of Cow urine ark in guinea pigs fed with a high cholesterol diet - Hiren Manubhai Chawda; Divyesh Rasiklal Mandavia; Seema Natvarlal Baxi; Vishalkumar Kishorbhai Vadgama; Chandrabhanu Rajkishor Tripathi (Mashhad University of Medical Sciences, 2014)
Objectives: Cow urine ark (CUA), known as "Amrita" as mentioned in Ayurveda, contains‎ anti-hyperglycemic and antioxidant effects. Therefore, we designed the present study to evaluate the lipid ‎lowering activity of CUA and its possible implication in metabolic syndrome.‎ Materials and Methods: Thirty guinea pigs of either sex were divided into five groups: Group 1 and 2 serving as a vehicle ‎and sham control, received normal and high fat diet for 60 days respectively; Group 3, 4 and 5 ‎received high fat diet for 60 days with CUA 0.8 ml/kg, 1.6 ml/kg and rosuvastatin (1.5 mg/kg) on the‎last 30 days of study period, respectively. Serum lipid profile (total cholesterol, triglycerides, LDL-‎C, VLDL-C, HDL-C, total Cholesterol/HDL-C) and serum enzymes (ALT, AST, ALP, LDH and CK-MB) ‎were performed in each group at the beginning and end of the study. Histological study of liver and ‎kidney was done in each group. Results: CUA (0.8 ml/kg) significantly decreased the serum triglycerides and VLDL-C, but CUA (1.6 ml/kg) ‎decreased the total serum Cholesterol, triglycerides and VLDL-C (p < 0.05). Higher dose (1.6 ml/kg) of ‎CUA also increased HDL-C level, significantly (p < 0.05). CUA reduced serum AST, ALP and LDH ‎level, which was statistically significant as well, while it also decreased the accumulation of lipid in hepatocytes as ‎compared to sham control.‎ Conclusions: CUA reduced triglycerides, increased HDL-C and found to be hepatoprotective in ‎animals that are on a high fat diet.